The effect of humor on the level of anxiety of uterine cancer patients undergoing hysterectomy - Negradas, Robelita C.
Cancer is one of the fatal diseases without a sure cure. In the Philippines, it is now being considered as the 4th leading cause of mortality. Uterine cancer, a malignancy that affects many women has a delibitating effect on quality of life. The effect ranges from physical to psychosocial, and the most common manifestations are fear, worry and anxiety. The diagnosis and management phase of cancer bring about such manifestations. Bio-behavioral interventions have proven effective in alleviating these feelings. One pf these interventions is humor therapy. Humor and laughter can counteract these negative thoughts or feelings. The power of humor, which consists of its physical, social, psychological and emotional functions has provided relief among many. It physiological function promotes a pattern of relaxation on the person, increases arterial and venous circulation promoting better circulation of oxygen, nutrients, immune elements and phagocytes, and it helps the body participate in the process of analgesia.Humor, considered universal, has long been a part of the Filipino culture. This makes this unique form of bio-behavioral therapy very applicable in our society.The study was done mainly to determine the effect of humor on the anxity level of uterine cancer patients who were scheduled for hysterectomy. Specific questions were:1. What is the humor profile of uterine cancer patients who were scheduled for hysterectomy?2. What is the socio-demographic profile of uterine cancer patients who were scheduled for hysterectomy?3. What is the relationship of the intervening variables, namely socio-demographic profile, role functions, support system, and spirituality to the uterine cancer patient's level of anxity?4. Is there a significant difference in the level of anxiety of uterine cancer patients who were scheduled hysterectomy before and after exposure to humor?5. Is there a significant difference in the level of anxiety of uterine cancer patients between the study and the control group?Twenty uterine cancer patients who have undergone hysterectomy had consented to become subjects in this study. They were admitted to the Philippine General Hospital Ward 14-B (Malignancy Ward). Purposive sampling was used in the selection of subjects. The assignment of participants was done in such a way that the first five clients who came in for hysterectomy were assigned to the control group first, the next five to study group, until the twenty samples were evenly assigned to the two groups.An assessment of anxiety level, humor and socio-demographic profile was done using a Likert type rating scale: State Trait Anxiety Inventory (STAI, by Spielberger) for anxiety, and Humor Assessment Tool (made by the investigator) for Humor. Included as a tool was a questionnaire on socio-demographic data. All tools were translated to Filipino, and they were pilot tested before finally used. The Filipino comedy films used to elicit laughter were the following: (1) "Home Along Da Riles," (2) "Tropang Trumpo," (3) "Mixed Nutrs," (4) "Bubble Gang".The interrupted time series with no treatment control group time series, was the type of quasi-experimental design used due to uncontrollable situations or variables during the data gathering period.T-test for two independent samples and analysis of variance (ANOVA) were the statistical tests used in testing the two hypotheses, and these were set at 0.5 and 0.10 level of confidence. Other statistical treatments were also applied, i.e. frequencies, percentages or rates and the Pearson Product Moment Correlation to determine if the intervening variables were related to the anxiety level of participants.
The following were the major findings of the study:1. The study and control groups were comparable in their humor profile scores which revealed that all of them had used humor in life.2. Tha ages of the participants' ranged from 27 to 59 years old with mean age of 42 years. Majority (17) belonged to the age bracket of 35 and above. Fourteen of the participants were married, four were widows, one was separated and one was single. From among the participants, fourteen had cervical cancer, while the remaining 6 had endometrial cancer.3. Majority have reached elementary level of education.4. In terms of occupational status, majority were jobless and dependent on the spouse for financial support. Most respondents had a family monthly income of P2,000.00 and below.5. Age was the intervening variable that was related to the anxiety level of the clients.6. There was a significant difference on the level of anxiety before and after exposure of the participants to humor (Filipino comedy film).7. There was a significant difference on the patient's level of anxiety between the study and control group.The results of the study suggest, that humor as a bio-behavioral intervention is an effective approach in managing fear and anxiety.Recommendations based on the result are as follows:Nurses in clinical practice need to organize training seminars or programs on the concepts of humor and laughter so that they will be aware of its many functions in the field of health and illness.Nurses need to have a happy and smiling attitude coupled with good background knowledge and skills in taking care of patients who are under stress.In planning for care of the patients in relation to the utilization of effective coping strategies like the use of their sense of humor and laughter, the support system must be included.A review of the nursing curriculum in both undergraduate and graduate levels need to be conducted and the use of bio-behavioral strategies such as the use of humor and laughter must be strengthened.Nurses interested in research can replicate the study with larger sample size and use subjects having different diagnosis from the subjects in this study. They can also use other forms of humor to elicit laughter; and use other anxiety inventory tools that look into the holistic manifestations of anxiety.Nurses can create and develop humorous activities like the conception of humor rooms or humor therapy programs which can be of great use of patients and hospital staff and personnelThe administration or those in authority has to support the innovative and cost effective bio-behavioral programs being created by its personnel, which would not only be of benefit to the patient buth to other health professionals as well.Cultivating the patient's sense of humor and using humor in communication by all members of the health team must be practiced.
Thesis (Master of Arts in Nursing)--University of the Philippines Manila.
Keywords: Cancer -- Palliative treatment; Cancer -- Patients; Anxiety; Cancer -- Humor therapy